The Effect of Soil Preparation Methods on Rain Water Infiltration as The Basis of Irrigation Application for Dry Land Rice - Sri Widata; Driska Arnanto; Maria Theresia Darini; Yekti Maryani; Djoko Heru Pamungkas (The University of Lampung, 2023)
The purpose of this study was to determine the effect of land preparation methods on the soil infiltration which can be used as a basis for designing irrigation for dryland rice cultivation. The study was arranged in a completely randomized design (CRD) with three land preparation treatments, namely T0 (no tillage), T1 (hoeing), and T2 (hoeing plus loosening). Each treatment was carried out with three replication plots. Artificial rain was given with an average intensity of 4.61 mm/h for 120 min. Observations were made on the infiltration thickness and rainwater volume. Results showed that land preparation methods resulted in very significant differences in the cumulative infiltration depth and infiltration rate, where the T2 treatment caused the highest infiltration. During 120 minutes of rain, 331.83 liters of water volume was poured out and resulted in an average infiltration thickness of 7.3 cm for T0 (no tillage), 18.09 cm for T1 (hoeing), and 21,3 cm for T2 (hoeing plus loosening). The results also showed that cumulative infiltration (y) increased with rain water volume (x) that followd a logarithmic curve with an R2 value of more 94-98% for the three land preparation methods with order T2 > T1 > T0.Keywords: Rain, Tillage, Infiltration, Dry land, Rice